2014
DOI: 10.1097/mnm.0000000000000023
|View full text |Cite
|
Sign up to set email alerts
|

Safety and antitumor efficacy of 153Sm-EDTMP and docetaxel administered sequentially to patients with metastatic castration-resistant prostate cancer

Abstract: Prior administration of Sm-EDTMP does not cause additional toxicities for subsequent treatment with docetaxel and does not reduce the antitumor efficacy of the latter. This work justifies further investigations on the possible synergistic effects of combined strategies with the two agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Similarly, retrospective studies undertaken by a multidisciplinary team at our institution showed a possible synergistic effect on survival of Sm 153 EDTMP in combination with chemotherapy [16]. A subsequent Phase II study confirmed that the administration of docetaxel (75 mg/m 2 administered intravenously every 21 day for at least 6 cycles) after Sm 153 EDTMP (37 MBq/kg) did not induce additional toxicities and did not reduce the antitumor efficacy [17].…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Similarly, retrospective studies undertaken by a multidisciplinary team at our institution showed a possible synergistic effect on survival of Sm 153 EDTMP in combination with chemotherapy [16]. A subsequent Phase II study confirmed that the administration of docetaxel (75 mg/m 2 administered intravenously every 21 day for at least 6 cycles) after Sm 153 EDTMP (37 MBq/kg) did not induce additional toxicities and did not reduce the antitumor efficacy [17].…”
mentioning
confidence: 53%
“…Our experience with docetaxel in combination with agents that are notoriously more myelotoxic than Ra 223 suggests that this combined approach is feasible [17]. As proof, the first data from a Phase I study showed that the combination of Ra 223 (fivefold dose of 50 kBq/kg every 6 weeks) with docetaxel (60 g/m 2 every 3 weeks) appeared to be very well tolerated [25], and the next step in evaluating the efficacy is ongoing [27].…”
Section: Future Perspectivementioning
confidence: 96%
See 1 more Smart Citation
“…The nadir of platelet and white cell reductions was between 3 to 6 weeks after injection, with complete recovery by week 8-9 (15-18), less delayed and shorter in duration than with 89 Sr. There is no evidence regarding samarium improving OS when used as a single agent but this was hypothesized when 153 Sm is used sequentially or combined with docetaxel (19)(20)(21) or immunotherapy (22).…”
Section: Abstract 223 Ra Prolongs Overall Survival In Symptomatic Pamentioning
confidence: 99%
“…Vertebral column, ribs, pelvis and the skull are among the most common sites of involvement (4). Palliative measures include, alleviation of pain, avoiding adverse effects by lowering medication dose such as corticosteroids and opioids, and preservation of patient activity and functionality (2,5). Bone seeking radiopharmaceuticals which have a strong affinity for blastic foci of bone metastases have shown favorable results in addressing such instances of bone pain.…”
Section: Introductionmentioning
confidence: 99%